Arteriovenous Malformation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Three children, ages 5 to 9 years, with A-V malformations that ruptured after trivial head trauma, are reported from the Departments of Neurosurgery, University Medical School and Red Cross Hospital, Kumamoto City, Japan.